Analisis Tingkat Kesiapan Guru dalam Mengimplementasikan Teknologi Pembelajaran Berbasis Internet di Sekolah Menengah Kejuruan - Arief Kurniawan (Departement of Mathematics Education, 2021)
This study uses a qualitative approach to analyze teachers' readiness level in implementing internet-based learning technology at Vocational High Schools (SMK). The research was conducted at SMK Muhammadiyah 1 Playen Yogyakarta. This research method employs a qualitative approach to gain an in-depth understanding of the factors influencing teachers' readiness to implement internet-based learning technology in the learning process. Additionally, observations were conducted to understand better teaching practices involving Internet technology in the classroom environment. The results of this study indicate differences in readiness levels between productive and normative teachers in implementing internet-based learning technology. This research highlights the importance of providing adequate support for teachers in developing skills and understanding how to use technology at SMK Muhammadiyah 1 Playen.